Evaluation of respiratory rate monitoring performance using a home oxygen monitoring device among patients with interstitial lung disease and chronic obstructive pulmonary disease - Hamada, Satoshi; Handa, Tomohiro; Tanabe, Naoya; Sato, Susumu; Tanizawa, Kiminobu; Sato, Atsuyasu; Morita, Satoshi; Chin, Kazuo; Hirai, Toyohiro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Home monitoring devices have been developed to measure adherence to home oxygen therapy. In this study, we evaluated the performance of TeleOx®, a commercially available remote monitoring device, in comparison with polysomnography (PSG) in patients with interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD) and the factors that affected TeleOx® correct use. Methods: TeleOx® was connected on the patient or concentrator side. The oxygen flow rates were set at 1, 3, and 5 L/min. Intraclass correlation coefficient (ICC) (2,1) was used to determine the agreement between respiratory rate measured using TeleOx® and that measured using PSG, and the minimum acceptable level of reliability was >0.7. Results: In total, 22 patients (16 with ILD and 6 with COPD) were assessed. In patients with ILD, the detection rate of patients’ respiration assessed using TeleOx® did not change according to the device’s position. It increased from 53.5% to 79.0% by changing the position from the concentrator to the patient side in patients with COPD. The ICC (2,1) value indicated that TeleOx® had acceptable reliability at oxygen flow rates of 1 and 3 L/min regardless of the device’s position in patients with ILD (the concentrator side: 0.9 and 0.82, respectively; the patient side: 0.95 and 0.82, respectively), whereas that did only at the oxygen flow rate of 1 L/min and in connecting TeleOx® on the patient side in patients with COPD (0.73). Conclusion: The monitoring performance of TeleOx® differed according to its position, oxygen flow rates, and patients’ diseases.